Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given any $a\in [0,1]$, I would like to prove that there are $x,y$ in the Cantor set such that $y-x=a$. I need a hint or something, this question seems a little bit unintuitive for me.

Thanks a lot.

share|cite|improve this question

Hint: what is the base 3 representation of points in the cantor set?

share|cite|improve this answer
these numbers have a ternary expansion with only 0,s and 2's, as such 0,2202202 – user42912 Feb 23 '13 at 23:00

Have you seen the ternary expansion formulation of the Cantor set? The Cantor set is precisely those real numbers that have a ternary expansion consisting entirely of $0$s and/or $2$s. Your task, then, is equivalent to determine how to add such a number ($x$) to some non-Cantor element ($a$) of $[0,1]$ such that the resulting sum ($y$) is a Cantor element.

share|cite|improve this answer
how can I do this? for example if I have 0,7977, how can I add a cantor number to have a cantor number in this case? it seems impossible, thank you for your answer. – user42912 Feb 23 '13 at 23:03
Don't forget to put it into ternary form, not decimal. – Cameron Buie Feb 23 '13 at 23:41
ha yes of course, yes, you're right – user42912 Feb 24 '13 at 9:13

First remember that every number $\in [0,1]$ can be expressed in base 3 by $\sum_{k = 1}^{\infty}{\frac{\beta_k}{3^k}};\; \beta_k \in \{0,1,2\}$.


$A + B = \{a + b;\; a \in A,\; b\in B\}$

$A - B = \{a - b;\; a \in A,\; b\in B\}$

$|A - B| = \{|a - b|;\; a \in A,\; b\in B\}$

The question asked is equivalent to prove that $[0,1] = \{|x - y|; x, y \in K = Cantor\;set\}$.

We know that the elements of the Cantor set are the numbers $\in [0,1]$ that only have 0 or 2 in their base 3 representation.

The trick is to add 1 to x - y, and remember that because of the Cauchy series, $ 1 = \sum_{k=1}^{\infty}{\frac{2}{3^k}} $ in base 3:

$x - y + 1 = \sum_{k = 1}^{\infty}{\frac{\sigma_{xk}}{3^k}} - \sum_{k = 1}^{\infty}{\frac{\sigma_{yk}}{3^k}}+\sum_{k = 1}^{\infty}{\frac{2}{3^k}}; \sigma_{xk}, \sigma_{yk} \in \{0, 2\} \text{ Therefore:} \sum_{k = 1}^{\infty}{\frac{\sigma_{xk} - \sigma_{yk}+2}{3^k}}; \sigma_{xk} -\sigma_{yk} + 2 = \alpha_k \in \{0, 2, 4\}$

putting $t_k = \frac{\alpha_k}{2}: \sum_{k = 1}^{\infty}{\frac{\alpha_k}{3^k}} = 2\sum_{k = 1}^{\infty}{\frac{t_k}{3^k}}; \;t_k \in \{0, 1, 2\}$. In other words, every number $\in [0,1] \text{ is expressed by }\sum_{k = 1}^{\infty}{\frac{t_k}{3^k}}$. However, since we're multipling it by 2, every number $\in [0,2] \text{is expressed by} \sum_{k = 1}^{\infty}{\frac{\sigma_k}{3^k}}$ In conclusion:

$K - K + 1 = [0,2] \rightarrow K- K = [-1, 1] \rightarrow |K-K| = [0, 1]$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.